2017 IEEE/ACM 39th International Conference on Software Engineering (ICSE) 2017
DOI: 10.1109/icse.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing APIs Documentation and Code to Detect Directive Defects

Abstract: Abstract-Application Programming Interface (API) documents represent one of the most important references for API users. However, it is frequently reported that the documentation is inconsistent with the source code and deviates from the API itself. Such inconsistencies in the documents inevitably confuse the API users hampering considerably their API comprehension and the quality of software built from such APIs. In this paper, we propose an automated approach to detect defects of API documents by leveraging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 39 publications
1
65
0
Order By: Relevance
“…Chaparro et al [11] defined 154 recurrent patterns to describe observed behavior (OB), expected behavior (EB) and step to reproduce (S2R) in bug descriptions with the aim of detecting the presence (or absence) of these pieces of information in such kind of artifacts (i.e., bug descriptions). Zhou et al [45], [46] employed specific linguistic patterns for automatically detecting inconsistencies between API documents and source code. Frequent grammatical patterns (i.e., dependencies in which either the governor or the dependent is a code-like term) along with structural features were also used by Petrosyan et al [36] to discover tutorial sections that explain a given API type.…”
Section: Related Workmentioning
confidence: 99%
“…Chaparro et al [11] defined 154 recurrent patterns to describe observed behavior (OB), expected behavior (EB) and step to reproduce (S2R) in bug descriptions with the aim of detecting the presence (or absence) of these pieces of information in such kind of artifacts (i.e., bug descriptions). Zhou et al [45], [46] employed specific linguistic patterns for automatically detecting inconsistencies between API documents and source code. Frequent grammatical patterns (i.e., dependencies in which either the governor or the dependent is a code-like term) along with structural features were also used by Petrosyan et al [36] to discover tutorial sections that explain a given API type.…”
Section: Related Workmentioning
confidence: 99%
“…It tries to obtain enough collocations between each word/API and other APIs/words. 9. Default English stop words.…”
Section: Training Set Creationmentioning
confidence: 99%
“…This approach is however constrained to Javadoc comments containing information about a method's parameters. Zhou et al devised an approach, similar to @TComment in terms of its application to method's parameter constraints and exception throwing declarations, that detects inconsistencies between API documentation and its source code by extracting documentation from Javadoc comments, analyzing documentation directives and performing a static analysis of the code of methods [61].…”
Section: Inconsistency Detectionmentioning
confidence: 99%